Genome Sequence of the Anaerobic, Thermophilic, and Cellulolytic Bacterium “Anaerocellum thermophilum” DSM 6725 - Kataeva, Irina A. (American Society for Microbiology (ASM), 2009)
“Anaerocellum thermophilum” DSM 6725 is a strictly anaerobic bacterium that grows optimally at 75°C. It uses a variety of polysaccharides, including crystalline cellulose and untreated plant biomass, and has potential utility in biomass conversion. Here we report its complete genome sequence of 2.97 Mb, which is contained within one chromosome and two plasmids (of 8.3 and 3.6 kb). The genome encodes a broad set of cellulolytic enzymes, transporters, and pathways for sugar utilization and compared to those of other saccharolytic, anaerobic thermophiles is most similar to that of Caldicellulosiruptor saccharolyticus DSM 8903.